2015
DOI: 10.1523/jneurosci.4557-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Transmission Is Mediated by the Excitatory GABA Receptor LGC-35 inC. elegans

Abstract: Under most circumstances, GABA activates chloride-selective channels and thereby inhibits neuronal activity. Here, we identify a GABA receptor in the nematode Caenorhabditis elegans that conducts cations and is therefore excitatory. Expression in Xenopus oocytes demonstrates that LGC-35 is a homopentameric cation-selective receptor of the cys-loop family exclusively activated by GABA. Phylogenetic analysis suggests that LGC-35 evolved from GABA-A receptors, but the pore-forming domain contains novel molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…This map of metabotropic gene-expression patterns delineates a significant portion of the second messenger communication system in the wiring diagram. In combination with previous work that identified the expression for the ionotropic GABA receptors (Bamber et al, 1999;Beg and Jorgensen, 2003;Gendrel et al, 2016;Jobson et al, 2015), we complete the map of the worm's GABA communication network (all GABA senders and recipients), revealing the surprising conclusion that even though <10% of all neuron classes release GABA, almost all neurons in C. elegans have the capacity to "listen" to GABA. Third, we perform whole-brain activity recordings to assess the nervous system response repertoire to repulsive and attractive stimuli from three distinct modalities: light, gustation, and olfaction.…”
mentioning
confidence: 87%
“…This map of metabotropic gene-expression patterns delineates a significant portion of the second messenger communication system in the wiring diagram. In combination with previous work that identified the expression for the ionotropic GABA receptors (Bamber et al, 1999;Beg and Jorgensen, 2003;Gendrel et al, 2016;Jobson et al, 2015), we complete the map of the worm's GABA communication network (all GABA senders and recipients), revealing the surprising conclusion that even though <10% of all neuron classes release GABA, almost all neurons in C. elegans have the capacity to "listen" to GABA. Third, we perform whole-brain activity recordings to assess the nervous system response repertoire to repulsive and attractive stimuli from three distinct modalities: light, gustation, and olfaction.…”
mentioning
confidence: 87%
“…Increasing concentrations of ethanol flatten the amplitude of body‐bending and decreases speed of movement (Davies et al , ). We recently reported that LGC‐35 regulates locomotor body bending and movement speed in C. elegans (Jobson et al , ). Specifically, deletion of LGC‐35 results in exaggerated body bending and increases animals' speed of movement.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike GABA A -ρ receptors, the vast majority of GABA A receptors are hetero-oligomers composed of three distinct subunits, with the (α 1 ) 2 (β 2 ) 2 (γ 2 ) 1 combination being the most abundant in the human brain (Sigel and Steinmann, 2012). Moreover, EXP-1 and LGC-35 are not expressed in the same cells in vivo further supporting that these receptors do not act as hetero-oligomers (Beg and Jorgensen, 2003;Jobson et al, 2015). Second, dose-response relationships reveal that most of the partially folded GABA analogues tested either showed no agonist activity (nipecotic acid, IMA and P4S) or were weak partial agonists (muscimol and isoguvacine) at both EXP-1 and LGC-35.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…These inconsistencies, along with the fact that many mutations in the charge-selectivity filter region of these channels nearly abolish channel expression (5,8), have led to a confusing picture that becomes increasingly more blurred as new mutational data are added (9,10) and new nonvertebrate genomes are sequenced (e.g., refs. [11][12][13][14][15]. Indeed, although much effort has been devoted to the identification of the mechanism underlying the cation-versus-anion selectivity of these channels, a careful analysis of the literature reveals that a large number of discrepancies exist, that disparate…”
mentioning
confidence: 99%